Trick pony - Lockard, Greg (Dark Horse Books, a division of Dark Horse Comics LLC, 2024)
"From the GLAAD Media Award-nominated writer of the bestselling queer historical graphic novel LIEBESTRASSE comes this LGBTQA+ fantasy tale of a washed-up rodeo star heading home to visit his father in the hospital. While on the road he confronts the mistakes of his past and the monsters of his present. A beautiful story that blends together themes of second chances, magical realism, queer romance, and fantasy."--Publisher.